Control is not a four-letter word! : establishing positive classroom behavior for the year in the first five days - Clancy-Ballard, Sarah, 1944- (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
"Teaching is the most important career. It is in the classroom that the youth of today can be provided with the tools to become a positive part of their society. Whether they are successful or not will determine the fate of our civilization. Regrettably neither social nor economic indicators' reflect the importance of the role of the educator. Teacher training rarely prepares the individual for their role.The goal of this manual is to begin correcting the negative situations, in any teaching scenario, by contacting the Educational Departments at colleges and universities as well as administrators (state, county, city, town level) Having a "how to" manual for these different venues would be desirable for teacher preparation. It is structured for each individual to read and customize to the needs of the individual teacher and students" -- Provided by publisher.
Keywords: Classroom management -- Handbooks, manuals, etc -- United States.; Teachers -- Training of -- United States.; Effective teaching -- United States.; Education -- Teaching -- Methods & Strategies.; Teaching skills and techniques.; elektronické knihy; electronic books